145k views
2 votes
Help Pls
I need done soon as possible

Help Pls I need done soon as possible-example-1
User RandomSeed
by
5.3k points

1 Answer

2 votes

Answer:

see explanation

Explanation:

given the 2 equations

4x + y = 2 → (1)

- 2x + y = 5 → (2)

Eliminate the term in y by subtracting (2) from (1) term by term

(4x - (- 2x) + (y - y) = (2-5)

6x = - 3 ( divide both sides by 6 )

x =
(-3)/(6) = -
(1)/(2)

substitute this value into either (1) or (2) and solve for y

(1) : - 2 + y = 2 ( add 2 to both sides )

y = 4

solution is ( -
(1)/(2), 4)

User Dnang
by
5.4k points